Development of World Englishes-Based Listening Materials to Raise the Awareness of the Varieties of English for Thai EFL Upper Secondary School Students - Passakornkarn, Supassorn; Vibulphol, Jutarat (LEARN Journal: Language Education and Acquisition Research Network, 2020)
English language usage has increased in all areas of the world over the past few decades, and goals for learning English as a second language have changed from ‘obtaining native-like proficiency’ to ‘gaining proficiency in dealing with English varieties’ (Graddol, 2006). English as a foreign language (EFL) Thai students should be provided with opportunities to raise their awareness of the many English language varieties. World Englishes-based listening instructional materials can be developed and used in English classes to increase awareness of English language varieties for Thai upper secondary school students. Hello, World Englishes! was developed using the framework proposed by Jolly and Bolitho (2011) and Marlina (2013) and positively evaluated by experts and teachers as practitioners in the relevant field. All the experts and teachers noted the necessity for such listening materials and agreed that they could be used to increase awareness of the English language varieties for secondary school students in Thailand.